Effects of vasopressor agents on the development of pressure ulcers in critically ill patients: a systematic review. (2nd March 2022) - McEvoy, Natalie; Patton, Declan; Avsar, Pinar; Curley, Ger; Kearney, Cathal; Clarke, Jennifer; Moore, Zena
Abstract : Objective: The primary objective of this systematic review was to determine the effect of vasopressor agents on the development of pressure ulcers (PUs) among critically ill patients in intensive care units (ICUs). The secondary outcome of interest was length of stay in the ICU. Method: A systematic review was undertaken using the databases searched: Medline, Embase, CINAHL and The Cochrane Library. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used to formulate the review. Data were extracted using a predesigned data extraction table and analysed as appropriate using RevMan. Quality appraisal was undertaken using the EBL Critical Appraisal Tool. Results: The inclusion criteria were met by 13 studies. Two studies provided sufficient data to compare the number of patients who developed a PU with and without the use of vasopressors. Consistently, within these two studies, being treated with a vasopressor increased the likelihood of PU development. RevMan analysis identified that shorter duration of administration of vasopressors was associated with less PU development (mean difference (MD) 65.97 hours, 95% confidence interval (CI): 43.47–88.47; p=0.0001). Further, a lower dose of vasopressors was also associated with less PU development (MD: 8.76μg/min, 95% CI: 6.06–11.46; p<0.00001). Mean length of stay increased by 11.46 days for those with a PU compared to those without a PU (MD: 11.46 days; 95% CI: 7.10–15.82; p<0.00001). The overall validities of the studies varied between 45–90%, meaning that there is potential for bias within all the included studies. Conclusion: Vasopressor agents can contribute to the development of PUs in critically ill patients in ICUs. Prolonged ICU stay was also associated with pressure ulcers in this specific patient group. Given the risk of bias within the included studies, further studies are needed to validate the findings of this review paper.